1969
DOI: 10.12669/pjms.313.7372
|View full text |Cite
|
Sign up to set email alerts
|

Imipenem Resistant Pseudomonas: The fall of the final quarterback

Abstract: Objective:To isolate, determine the frequency, and study the demographic trends of MBL positive Pseudomonas aeruginosa from imipenem resistant isolates collected from clinical samples in a tertiary care hospital of Pakistan.Methods:In this cross sectional study a total of 230 strains of Pseudomonas were isolated from various clinical specimens on the basis of culture and biochemical tests. Imipenem resistant isolates were selected by Kirby Bauer Diffusion technique, followed by screening for MBL production by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 15 publications
2
14
3
Order By: Relevance
“…53 However, findings similar to the results of this study were reported from Pakistan, in a study done by Ameen et al, which showed that out of 230 investigated strains of P. aeruginosa, 49.5% were imipenem-resistant. 54 Internationally, most of the European countries such as Austria, Belgium, Denmark, Finland, France, Germany, Iceland, Luxemburg, Malta, and the Netherlands reported prevalences of resistant isolates below 20%, However, in some countries such as Romania and Greece reported figures are approximately similar to our findings, with more than 45% being resistant. 55 The emergence and dissemination of IRPA is of importance because these isolates show resistance to multiple antibiotics simultaneously, hence, physicians in the majority of Iranian hospitals, as shown by the results of this study, may face difficulties in the treatment of IRPA infections.…”
Section: Discussionsupporting
confidence: 84%
“…53 However, findings similar to the results of this study were reported from Pakistan, in a study done by Ameen et al, which showed that out of 230 investigated strains of P. aeruginosa, 49.5% were imipenem-resistant. 54 Internationally, most of the European countries such as Austria, Belgium, Denmark, Finland, France, Germany, Iceland, Luxemburg, Malta, and the Netherlands reported prevalences of resistant isolates below 20%, However, in some countries such as Romania and Greece reported figures are approximately similar to our findings, with more than 45% being resistant. 55 The emergence and dissemination of IRPA is of importance because these isolates show resistance to multiple antibiotics simultaneously, hence, physicians in the majority of Iranian hospitals, as shown by the results of this study, may face difficulties in the treatment of IRPA infections.…”
Section: Discussionsupporting
confidence: 84%
“…Pseudomonas spp. was the second most prominent pathogen associated with the acquisition of imipenem resistance, with a frequency of 61.89%, and has been noted in other reports from Pakistan, presenting imipenem resistance rates of 13.42% in 2011 and of 28% and 49.5% in 2015, thus demonstrating a sharp rise in the frequency of imipenem resistance [ 49 , 51 , 52 ]. The victims of Pseudomonas spp.…”
Section: Discussionmentioning
confidence: 64%
“…Various mechanisms could be responsible for carbapenems resistance in P. aeruginosa including the decrease in the permeability of the cell-wall, intrinsic efflux systems over-expression in addition to production of hydrolyzing enzymes particularly MBLs. The presence of MBLs is responsible for about 40% of IRPA isolates all over the world; 39% in a surveillance program in Italy [29] and 40% in Portugal [30], with higher rates reported in Pakistan (764.9%) [31] and remarkably lower rates in France (5.6%) [32].…”
Section: Discussionmentioning
confidence: 99%